ENHANCING THE ABILITY OF CLASSROOM TEACHERS IN IMPLEMENTING THE LEARNING USING MEDIA INTERACTIVE CD-BASED INTEGRATED SCIENCE EDUTAINMENT THROUGH THE IMPLEMENTATION OF SUPERVISION WITH THE TECHNIQUE OF DEMONSTRATION TEACHING IN SDN MEDOKAN AYU I/270 SURABAYA - Enniek Dwi Nurhayati (LPPM STAI Muhammadiyah Probolinggo, 2021)
The presence of the media is essential in teaching and learning. In the process of unclearness of the material presented, you can help by introducing the media as an intermediary. The complexity of the material presented can be simplified with the help of media. The media can present what the teacher cannot express with certain words or sentences. Even material abundance can be concretized by the presence of mass media. Thus, it is easier for students to assimilate the materials than without the help of the media. The authors would like to perform School Action Research at SDN Medokan Ayu I/270 Surabaya with the title